Eficiência reprodutiva de vacas nelore primíparas em anestro submetidas à progestágenos após a iatf - Marcell Pinto Brandão (2023)
The objective was to evaluate the efficiency of different forms of application of exogenous progesterone on the pregnancy rate in primiparous Nelore cows in anestrus. The experiment was carried out at Fazenda Rancho de Casta - Nelore Bem Bom, located in the municipality of Iuiú, southwest region of Bahia. A total of 116 primiparous Nelore cows, 90 days after calving, were submitted to a fixed-time artificial insemination (FTAI) protocol.On day zero (D0), the synchronization protocol was started by inserting an intravaginal P4 release device (PRIMER®, Agener, 1.0g of progesterone) associated with 2.0 mg of Estradiol Benzoate (RIC-BE® ,Agener, 1mg/mL) intramuscularly (IM). Nine days (D9) after 08:00 h, the P4 device was removed and 500μg of Cloprostenol Sodium (ESTRON®, Agener, 0.25mg/mL, IM) was administered; 0.6mg of Estradiol Cypionate (ECP®, Pfizer, 2mg/mL, IM) and 300UI of Equine Chorionic Gonadotropin (NOVORMON®, Zoetis, 200UI/mL, IM). After FTAI, the animals were distributed into four treatments: T1 (control: no hormone treatment after FTAI), T2 (application of 150 mg of long-acting P4 intramuscularly 4 days after FTAI), T3 (use of single-dose intravaginal device 1 g slow-release intravaginal device for 7 days from the 4th day after TAI), T4 (use of the 1 g slow-release intravaginal device for 7 days from the 4th day after TAI). The concentration of progesterone (P4), size of the preovulatory follicle (TFO) and the corpus luteum (TCL) were evaluated. Pregnancy diagnosis was performed by transrectal ultrasonography 30 days after TAI. Data were subjected to analysis of variance (ANOVA), and means compared by the Tukey test at 5% significance. The effect of time (DG11 and DG30) was evaluated in a split-plot design. The pregnancy rate was subjected to the chi-square test. There was no significant difference between the pregnancy rate at 30 days, being T1 (59.26%), T2 (58.62%), T2 (65.52%) and T4 (51.72%). There was no effect of the treatments on the concentration of P4, TFO and TCL which presented an average of 3.39 for D11 and 2.26 for D30, 12.34; 21.25 respectively. There was no significant difference between treatments, but it is possible to verify that the single-dose intravaginal device allowed a higher pregnancy rate, in numerical terms, at 30 and 60 days. It is necessary to point out that the conditions of the study allowed a high pregnancy rate (>50%) in all treatments. Supplementation with exogenous P4 after FTAI did not increase reproductive efficiency. It is concluded that the administration of exogenous P4 intramuscularly or through a slow-release intravaginal implant did not promote an increase in the diameter of the corpus luteum or in the serious concentration of progesterone, as well as it did not increase the pregnancy rate 30 and 60 days after FTAI in primiparous Nellore cows in anestrus with calf at foot.